Folhas de amoreira tratadas com vitamina e esterol e seus efeitos em parâmetros biológicos de Bombyx mori L. - De Bortoli, Sergio Antonio [UNESP]; Takahashi, Roque [UNESP]; Miranda, José Ednilson; Dias, Luciane Sandrini; De Bortoli, Caroline Placidi; De Bortoli, Sergio Leandro Placidi (My University, 2012)
This study aimed to evaluate the effects of adding different concentrations of the leaf additives nandrolone decanoate, ascorbic acid, retinol palmitate and retinol acetate on biological parameters of Bombyx mori larvae. The results showed that nandrolone and ascorbic acid, both at 0.5%, provide the best value for the development of the larvae of B. mori, values which do not correspond to significant increases in cocoon and silk production; 1.0% of retinol palmitate show negative effect to larvae development.
Effects of mulberry leaves treated with vitamin and esterol affect biological parameters of Bombyx mori L.
Keywords: Anabolic steroid; Larvae development; Silk production; Silkworm; Vitamin A; Vitamin C